Две могилы с погребениями женщин из могильника Нейзац - Храпунов, И.Н. (Материалы по археологии, истории и этнографии Таврии, 2007)
Могильник Нейзац расположен в центре предгорной зоны Крыма, в долине реки Зуя, приблизительно в 25 км к юго-востоку от Симферополя. Его систематические раскопки ведутся с 1996 г. К началу 2006 г. на территории могильника исследовано 299 погребальных сооружений, в том числе склепы, подбойные и грунтовые могилы. The cemetery of Neizatz is situated in the centre of the foothill zone of Crimea, in the valley of the Zuya River, approximately at the distance of 25 kilometers to the south-east from Simferopol. Regular excavations have been carried out since 1996. By the beginning of 2006, 299 burial constructions were investigated on the territory of the cemetery: they included vaults, shaft-and-chamber graves and ground graves. Basing on the materials of excavations, two culture-chronological horizons of the monument were distinguished. The first one is dated back to the period till the mid-3rd century AD; it is presented mainly by shaft-and-chamber and ground graves. The second one is dated back to the 4th' century AD, when the majority of burials were performed in vaults; first of them appeared even in the first half of the Зrd century AD.